2017
DOI: 10.1021/acs.jafc.7b02880
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester (Propolis Extract) Ameliorates Insulin Resistance by Inhibiting JNK and NF-κB Inflammatory Pathways in Diabetic Mice and HepG2 Cell Models

Abstract: Caffeic acid phenethyl ester (CAPE), extracted from propolis, was evaluated for the ameliorative effects on insulin resistance and the mechanisms were identified, using non-insulin-dependent diabetes mellitus (NIDDM) model mice and insulin resistance (IR) model cells. After 5 weeks of CAPE supplementation, insulin sensitivity, hyperlipidemia, and peroxisome proliferator-activated receptor-α (PPAR-α) levels were improved in mice. Proinflammatory cytokines in serum and the expressions of tumor necrosis factor-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 37 publications
3
58
0
1
Order By: Relevance
“…Obesity and hepatic steatosis are connected with lipid metabolic syndrome and inflammation (Ahmed et al, 2010;Ghazani & Marangoni, 2013;Han et al, 2013). Therefore, it is important to study edible oil and their active components to prevent lipid metabolic syndrome or disease (Nie et al, 2017). It has been reported that eating canola oil instead of sunflower oil could improve lipid disorder in type II diabetic women (Salar, Faghih, & Pishdad, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and hepatic steatosis are connected with lipid metabolic syndrome and inflammation (Ahmed et al, 2010;Ghazani & Marangoni, 2013;Han et al, 2013). Therefore, it is important to study edible oil and their active components to prevent lipid metabolic syndrome or disease (Nie et al, 2017). It has been reported that eating canola oil instead of sunflower oil could improve lipid disorder in type II diabetic women (Salar, Faghih, & Pishdad, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that in the setting of obesity, peripheral adipose tissue increased inflammatory cytokines production such as tumor necrosis factors-alpha (TNF-α), monocyte chemotactic protein (MCP-1), and interleukin (IL)-6, which have important effect on insulin resistance and lipid metabolism, except promoting inflammation (Arrese, Cabrera, Kalergis, & Feldstein, 2016;Hotamisligil et al, 1993;Younce & Kolattukudy, 2012). Obesity and hepatic steatosis can induce proinflammatory cytokines TNF-α, MCP-1, and IL-6, which regulated by oxidative stress and NF-κB pathways (Nie et al, 2017;Quan, Jiang, Xue, Zhu, & Wang, 2011). However, there is no available treatment for hepatic steatosis; thus, daily eating habits are particularly crucial to prevent hepatic steatosis, especially the choice of the edible oils.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we determined that an insulin concentration of 10 μg/ml applied to HepG2 and LO2 cells for 48 h resulted in the lowest glucose consumption while cell viability was unaffected. In previous studies, glucose consumption in normal cells was used as the control [24,25], but we found that insulin has a mitogenic effect on hepatocytes, although there were no changes in proliferation rate within a certain concentration range. This has also been described by other investigators [31,32].…”
Section: Discussionmentioning
confidence: 95%
“…The liver synthesizes, stores, and releases glycogen, which is important for glucose metabolism. Therefore, HepG2 cells are an ideal cell model for investigating the mechanisms of IR and testing the efficacy of hypoglycemic drugs [24,25]. We also used LO2 cells, which are normal hepatocytes, for further validation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The glucose uptake was determined as previously reported with some modification (Nie et al, 2017). Briefly, HepG2 cells (4 × 10 4 cells/well) were cultured in a chamber slide (Thermo Scientific, Waltham, MA, USA).…”
Section: Glucose Uptake Assaymentioning
confidence: 99%